On the extreme points of some classes of holomorphic functions - Nicolas Samaris (International Journal of Mathematics and Mathematical Sciences)
Let U be the unit disk, D⊃U an open connected set and z0∈D. Let also P(z0,c,D) be the class of holomorphic functions in D for which f(z0)=c and Ref(z)>0 in U. We find the extreme points of the class P(z0,c,D).